THE EFFECTIVENESS OF E-PUSKESMAS APPLICATION ON EMPLOYEE PERFORMANCE IN SINDANG BARANG PUSKESMAS BOGOR: EFEKTIFITAS APLIKASI E-PUSKESMAS TERHADAP KINERJA PEGAWAI DI PUSKESMAS SINDANG BARANG KOTA BOGOR - Bunga Oktora; Sasni Triana Putri (Jurnal Ilmiah Wijaya, 2018)
The needs for fast and accurate information becomes a demand in all aspects of life in the era of globalization. As long with advances information and communication technology, conventional service system that has been applied in government shifted into electronic based service system. Epuskesmas application has been running in 670 puskesmas, and 25 of public health office arround Indonesia. In February 2017, Public health office Dinas in district and Bogor has been integrated with this e-puskesmas application by covering 102 puskesmas. To knowing the effectiveness epuskesmas application to employee’s performance at Puskesmas Sindang Barang Kota Bogor 2017. The research design used descriptive analytic quantitative with cross sectional approach. The population sample of this research was employee at Puskesmas Sindang Barang Kota Bogor which amounted to 20 respondents, with sampling technique used is total sampling. Data were analyzed univariate and bivariate. From 20 respondents, 8 people (40%) have effective usage and there are 12 people (60%) ineffective usage, and 9 people (45%) with good performance and 11 people (55%) with poor performance. Obtained p value= 0,028 with significant value is <0,05, so Ha is accepted. The result of statistical test showed that, there is an effectiveness e-puskesmas application to employee’s performance at Puskesmas Sindang Barang Kota Bogor 2017. It is expected to be a learning material for Puskesmas employee’s, in order to increase the knowledge and ability for using e-puskesmas application to employee’s performance at Puskesmas Sindang Barang Kota Bogor 2017.